The Quest for Liberation in South Africa: Contending Visions and Civil Strife, Diaspora and Transition to an Emerging Democracy - Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2012)
Introduction: Purpose of this contribution To write an inclusive history of liberation and transition to democracy in South Africa is almost impossible. To do so in the course of one paper is even more demanding, if not daunting. Not only does "the liberation struggle" in South Africa in its broadest sense span more than a century. It also saw the coming and going of movements, the merging and evolving of others and a series of principled and/or pragmatic pacts in the process. The author is attempting here to provide a rather descriptive (and as far as possible, chronological) look at and rudimentary outline to the main organisational levels of liberation in South Africa since roughly the 1870’ s. I will draw on my own work in the field over the past fifteen years as well as other sources. A wide variety of sources and personal experiences inform this contribution, even if they are not mentioned here. Also needless to say, one’s own subjectivities may arise – even if an attempt is made towards intersubjectivity.